Early modern women writers engendering descent - Loughlin, Marie H., 1962- author.
1 online resource (312 pages).
Keywords: Focusing on Mary Sidney Herbert and Mary Sidney Wroth⁰́₉s use of the figures of origin, descent, and inheritance in their poetry and prose, this book examines how these central women writers situated themselves in terms of early modern England⁰́₉s rich ancestral cultures, employing these and other genealogical concepts to talk about authorship, family, selfhood, and memory. In turn, both Sidney Herbert and Sidney Wroth also shaped their works in relation to the ways in which writers within their familial communities and literary coteries constructed them as Sidneys, heirs, descendants, and future ancestors, in genres ranging from the patronage dedication and pastoral eclogue to mythographic genealogia and georgic poetry. In the intersection of ancestry, death, sexuality, and reproduction, the book contends that Sidney Herbert and Sidney Wroth develop their authorship within the simultaneous rigidity and flexibility of their world⁰́₉s genealogical discourses.